ChemInform Abstract: An Element Through the Looking Glass: Exploring the Au‐C, Au‐H and Au‐O Energy Landscape. Issue 6 (21st January 2016) - Rosca, Dragos‐Adrian; Wright, Joseph A.; Bochmann, Manfred
Abstract: Review: emphasis on recently discovered gold(III) complexes with bonds to hydrogen, oxgen, alkenes and CO ligands; 206 refs.